Concepções sobre a aprendizagem baseada em problemas: um estudo de caso na Famema - Moraes, Magali Aparecida Alves De; Manzini, Eduardo José [UNESP] (Associação Brasileira de Educação Médica, 2006)
This case study approaches the different conceits existing with respect to the development and implementation of Problem Based Learning (PBL) at the Faculty of Medicine of Marília (Famema). The aim of this study was to analyze the opinions of managers-professors, tutorial-professors and first year students of the Medical Course about this methodology in the curriculum of Famema and its relationships with medical education. Data were collected by means of semistructured interviews. The guidelines for the interviews were analyzed by referees, and a pilotstudy was carried out for adapting them. The interviewed persons were two managers, twelve tutorial-professors and twelve first year medicine students from Famema in 2002. The interviews were analyzed using thematic content analysis. Two referees evaluated the thematic categories and the level of agreement with the researcher was 94.8% and 97.43% respectively. The thematic categories were: PBL at Famema and medical education and PBL Analysis of the data allowed concluding that 1) the educational process at Famema was built collectively; 2) teaching-learning and the professional practice are dynamic contexts, with plenty of contradictions and different opinions; and 3) continued capacity building for tutorial professors is a necessar y resource that should be extended to the professional practice of health professionals.

O trabalho constitui um estudo de caso que aborda as versões sobre a implementação e desenvolvimentoda Aprendizagem Baseada em Problemas (ABP) na Faculdade de Medicina de Marília (Famema).O objetivo da pesquisa foi analisar as concepções de docentes-gestores, docentes-tutores e estudantes da 1ª série do curso de Medicina sobre essa metodologia no currículo da Famema e sua relação com a formação médica. Os dados foram coletados por meio de entrevistas semi-estruturadas.Os roteiros das entrevistas foram analisados por juízes, e um estudo piloto foi realizado para asua adequação. As entrevistas foram realizadas com dois gestores, 12 docentes-tutores e 12 estudantes da 1ª série do curso médico da Famema em 2002. O método utilizado para a análise das entrevistas foi o de análise de conteúdo temática. Após a elaboração das classes temáticas, estas foram avaliadas por dois juízes, e o índice de concordância com a pesquisadora foi de 94,8% e 97,43%, respectivamente. Foram definidas duas temáticas: a ABP na Famema, e a formação médica e a ABP.A análise dos dados permite considerar que: 1) o processo educacional realizado na Famema tem sido construído coletivamente; 2) o contexto de ensino-aprendizagem e da prática profissional é dinâmico e cheio de contradições e opiniões diferentes; 3) a educação permanente para os docentes é um recurso necessário, que precisa ser estendido à prática profissional dos profissionais de saúde.
Conceits about problem based learning: a case study at Famema
Keywords: Problem Based Learning; Education; Medical Education; Teaching; Learning; Curriculum; Faculty,Medical; Aprendizagem Baseada em Problemas; Educação; Educação Médica; Ensino; Aprendizagem; Currículo; Docentes de Medicina